Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Seasonal–diurnal nonlinear and interactive associations between built–natural–topographic indicators and land surface temperature in a coastal urban agglomeration - Aifang Weng; Baoyin Li; Yuying Lin; Linsheng Wen; Sunbowen Zhang; Chuanmao Hua; Chengshu Ke; Yilin Zou (Energy and Buildings, 2026)

Spatiotemporal inequities in early-life ecological liveability and sleep health in preschool children - Yongzhou Liang; Hao Pan; Qiyan Chen; Huizhen Li; Xinyi Weng; Mengqiu Cao; Huiyu Zhou; Nahid Mohajeri; Lin Wang; Tianren Yang; Jing Hua (Environmental Pollution, 2026)

Quintuple-stimulus responsive Ti3C2Tx-silk nanofiber@Fe3O4/polymer bilayer actuators for programmable soft robotics and non-contact intelligent transportation - Kaihuai Yang; Zhen Wang; Junjie Lin; Wanling Cai; Sitong Zeng; Peidi Zhou; Mingcen Weng (Chemical Engineering Journal, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Material flow and sustainable utilization of end-of-life motorcycles under Taiwan’s vehicle electrification policy - Hsin-Tien Lin; Kuo-Che Weng; Daniel Sebastián Castillo-Castro (Waste Management, 2026)

Discrimination of gold deposit types based on big data analysis and machine-learning techniques - Lihao Feng; Qingfei Wang; Daniel D. Gregory; Lin Yang; Yunyun Niu; Guodong Zhu; Huajian Li; Hesen Zhao; Weijun Weng (Journal of Asian Earth Sciences, 2026)

Built-in electric field-driven d-band engineering in metal sulfide heterojunctions for high-efficiency electro-Fenton degradation of antibiotics - Xiangwei Zou; Yue Wang; Xinyu Wang; Lin Lin; Xiao-yan Li; Chitou Lei; Xiaojun Fan; Weng Ian Ieong; Qinfen Gu; Lianpeng Sun; Chao Yang (Chemical Engineering Journal, 2026)

Characterization and classification of a novel bacteriophage, vB_RsoP_HXg1W, infecting Ralstonia pseudosolanacearum: a new member of the genus Serkorvirus in the family Autotranscriptaviridae - XiaoLi Yu; Zheng Fang; Qingshan Wu; Rui Wu; Chuangen Lin; Lan Xiang; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2026)

Electron Beam Irradiation Elicits Dose-Dependent Physio-Biochemical Responses and Antioxidant Defense Modulation in Sugarcane (Saccharum spp. hybrid) - Hai-Rong Huang; Kai-Chao Wu; Meng-Ling Weng; Krishan K. Verma; Tian Pang; Ling-Ling Liang; Zhi-Nian Deng; Lin Xu (Sugar Tech, 2026)

ADAMTS7 selective inhibitor BAY-9835 alleviates acute myocardial infarction by suppressing the NF-κB-mediated pyroptosis - Yunzhi Ling; Yang Lyu; Hanchuan Chen; Biting Lin; Gengyu Zhou; Simiao Chen; Tingting Weng; Ziqing Ruan; Yuanfan Zhu; Zhaoju Zhu; Yansong Guo; Kaiyang Lin (Toxicology and Applied Pharmacology, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Multifunctional BQD interlayer enables high-resolution high-efficiency QLEDs:Eliminating EML void defects and optimizing interfacial carrier transport - Yue Chen; Yuting Bai; Zunxian Yang; Luxi Yuan; Ye Chen; Xudong Jiang; Jiajie Hong; Benfang Liu; Zhiyu Yuan; Jinzhu Gao; Zhezhou Fang; Runsen Yu; et al. (Chemical Engineering Journal, 2026)

Effects of varying temperature and salinity levels on the emission of short-lived halocarbons and dimethyl sulfide from selected tropical green seaweeds - Tinesa Krishnan; Fiona Seh-Lin Keng; Siew-Moi Phang; Choon-Weng Lee; Yee-Jun Tham; Hui-Yin Yeong; Chui-Wei Bong; Gill Malin (Algal Research, 2026)

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

Development and validation of a prognostic nomogram for predicting the progression risk of HCC after lenvatinib therapy - Chen Xie; Shaohong Luo; Shen Lin; Xiaoting Huang; Xiuhua Weng; Xiongwei Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plant 3D-2D-ResNet-SE: Monitoring the changes of leaf water content and chlorophyll in Betula luminifera seedlings during drought stress - Hao Liang; Shuai Ma; Xiange Hu; Nan Wang; Haoqi Liu; Yuhui Weng; Erpei Lin; Huahong Huang; Xiongwei Lou (Computers and Electronics in Agriculture, 2026)

Anti-rheumatoid arthritis sesquiterpenoids from the roots of Lindera glauca - Siqi Li; Jiacheng Weng; Gang Li; Zheyuan Lin; Yu Zhou; Yuting Wu; Xiongyu Meng; Qi Shi; Guifen Zhou; Luping Qin; Huaqiang Li (Phytochemistry, 2026)

Sustainable production of ultrafine silver powder via a sulfate-mediated closed-loop process - Jianghao Chen; Guangsheng Zeng; Wei Weng; Xiaopeng Chi; Hengxing Zhang; Jiaozhong Cai; Junnan Chen; Xu Chen; Zhaojie Wang; Yuanxiang Lin; Shuiping Zhong; Wen Tan (Journal of Cleaner Production, 2026)

Unveiling mechanistic insights of inactivated Aspergillus niger spore by fishery-waste-derived chitosan via synchrotron radiation tomography - Ying-Chen Chen; Chih-Huang Weng; Chun-Chieh Wang; Zi-Jing Lin; Shang-Ming Huang; Girma Sisay Wolde; Jenn-Wen Huang; Mo Da-Sang Hua; Yao-Tung Lin (Carbohydrate Polymers, 2026)

Biodegradable mulch film-enriched with biochar, chicken feather, and oyster shell powder for improved soil quality and crop productivity - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Environmental Research, 2026)

Functionalized polymer carbon dots with multi-level trapping structures for capacitive energy storage across extreme temperatures - Xue Li; Ling Weng; Lizhu Guan; Houyu Wang; Xiaoming Wang; Xiaorui Zhang; Ruiqun Pan; Lin Zhang; Yuhan Li; Zijian Wu (Chemical Engineering Journal, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

Gypenosides as a potential bacteriostatic agent against Escherichia coli: dual mechanistic insights from host target network analysis and in vitro validation - Jingwei Pan; Runcheng Zhou; Wenjing Zhang; Kecan Chen; Jiaxi Liang; Jiahao Shen; Zhiteng Lin; Xumei Yi; Shanfan Weng; Xin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Quantifying evapotranspiration and shading cooling of urban vegetation across climates under extreme heat using an integrated SCOPE-SEB model and surface temperature analysis - Zhaowu Yu; Mingchuan Shao; Wenjun Yang; Yujia Zhang; Yuxia Hu; Wenjuan Ma; Junhong Zhong; Yanghan Lin; Mincong Wang; Huiwen Zhang; Jiquan Chen; Chenghao Wang; et al. (Remote Sensing of Environment, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

PLGA nanoparticles encapsulating fibroblast growth factor 21 alleviate acetaminophen-induced acute liver injury - Jie Lin; Guoxin Jin; Ling Zhang; Xiu Weng; Kecheng Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Investigating multi-scale associations and thresholds between eco-environment quality and urban landscape patterns: A case from coastal China - Linsheng Wen; Manuel Esperon-Rodriguez; Yun Peng; Aifang Weng; Yunrui Zhou; Sunbowen Zhang; Baoyin Li; Yuying Lin (Journal of Geographical Sciences, 2026)

Biotechnological upcycling of Laminaria japonica processing waste via Lactiplantibacillus plantarum fermentation: release and formation of antioxidant and tyrosinase-inhibitory compounds - Jing Wu; Haojie Lin; Rong Lin; Ritian Jin; Duo Liang; Zhongyang Ren; Wuyin Weng; Shen Yang (Food Chemistry, 2026)

Stabilization of oleogels using high internal-phase Pickering emulsions stabilized by myofibrillar proteins from large yellow croaker as a template: Effect of pH and transglutaminase - Zhongyang Ren; Qingqing Li; Min Lin; Yuan Zhao; Linfan Shi; Shuji Liu; Zhiyu Liu; Wuyin Weng (Food Chemistry, 2026)

Bioinspired membrane surface functionalization reshapes biofilm structure and nitrogen transformation pathways under carbon-limited conditions - Wei Zhang; Min Long; Xiong Zheng; Xianming Weng; Enwei Lin; Yang Wu; Yinguang Chen (Chemical Engineering Journal, 2026)

Multi active sites regulation of buried interface defects in n-i-p perovskite solar cells with tryptophan derivatives - Yanan Liu; Xinbao Lin; Xiaozheng Zhao; Tianci An; Wenya Zhao; Miaoran Zhang; Linfeng Cui; Taoyu Weng; Bo Liu (Chemical Engineering Journal, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

A revised MARCOS method for multi-index forest productivity assessment - Jian Lin; Junzhe Zhang; Peilin Weng (Environmental Monitoring and Assessment, 2026)

An LLM-driven estimation framework for estimating regional travel structures based on spatiotemporal multi-modal travel data - Huapeng Shen; Jiancheng Weng; Pengfei Lin (Sustainable Cities and Society, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

BMSC vesicles-encapsulated tannic acid-derived carbon dots efficiently target and orchestrate mitochondria mitophagy to promote cartilage repair in osteoarthritis - Rongjie Lin; Zhusong Huang; Weibin Chen; Quan Liu; Huiling Guo; Xingyu Lin; Yao Wang; Zhenbin Chen; Xi Zeng; Shishui Lin; Shaohuang Weng; Min Chen (Chemical Engineering Journal, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Research hotspots and evolutionary trends in microalgae-derived EPA production: A bibliometric review - Qingting Weng; Xiaoai Lin; Longzao Luo; Lang Tan; Qin Liu; Shiping Lu; Guosheng Li; Zhou Zhang (Algal Research, 2026)

Development of a visual rapid detection method for aquatic animal-derived Trypanosoma via MIRA-LFD - Xue-Mei Yuan; Xin-Zhi Weng; Xia-Lian Bu; Jing Chen; Jing-Biao Jiao; Xian-Qi Peng; Wei-Song Ma; Ling-Yun Lin; Lei Huang; Xiao-Yi Pan; Hong-Xia Hu; Ling-Wei Xu; et al. (Veterinary Parasitology, 2026)

Dynamics and trade-off/synergy of ecosystem services in China's First Batch national Parks: Evidence from recent decades and future land use and cover changes - Aifang Weng; Baoyin Li; Yuying Lin; Linsheng Wen; Yunrui Zhou; Guo Cai; Sunbowen Zhang; Mir Muhammad Nizamani; Hongxin Wang (Journal of Environmental Management, 2026)

Multifunctional chitosan/polyvinyl alcohol film enhanced with N-TiO2 and jaboticaba peel extract for shrimp freshness monitoring and banana preservation - Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Shang-Ming Huang; Jenn-Wen Huang; Chanat Chokejaroenrat; Dong-Hau Kuo; Yao-Tung Lin (Food Packaging and Shelf Life, 2026)

Shadow under the lamp: Evidence-based assessments reveal local extirpation risk of large Indian civets (Viverra zibetha) concealed by intensive activity in human-dominated landscapes - Weiming Lin; Yue Weng; Hongmin Wang; Minhui Li; Qi Wang; Jia A; Qing Zhao; Fang Wang (Biological Conservation, 2026)

The Potential Implications of Neutrophil to Albumin Ratio for Short-term Prognosis in Myasthenia Gravis Patients - Hai Lin; Shenyi Lin; Shengli Pan; Shengqi Li; Jinrong Zhu; Yukai Wang; Siyao Chen; Lingsheng Wang; Zhangjing Zhu; Shiyue Wang; Suwen Huang; Yiyun Weng (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Thickened active layer contribute less to vegetation growth over the Tibetan Plateau - Wenwen Li; Denghua Yan; Baisha Weng; Yuequn Lai; Wuxia Bi; Lin Zhu; Zhaoyu Dong; Yuhang Zhang; Jianyun Zhang; Hao Wang (Journal of Hydrology, 2025)

Differential modulation of aroma profiles in instant Oolong tea powder by two Aspergillus niger β-glucosidases - Ziyue Chen; Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Shuyi Weng; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2025)

Curcumin-loaded electrospun nanofiber film based on polyvinyl alcohol and myofibrillar protein for active packaging of strawberry - Junchao Huang; Zhiyu Li; Zijia Zhan; Jingzhao Feng; Zhijie Zheng; Yijing Wu; Shoukai Lin; Qibiao Weng; Jianyi Wang; Jie Yang; Yuting Tian (Food Packaging and Shelf Life, 2025)

Molecular planarity tailored hole-transporting materials for efficient perovskite solar cells - Xiaozheng Zhao; Xinbao Lin; Can Meng; Yanan Liu; Tianci An; Taoyu Weng; Linfeng Cui; Miaoran Zhang; Bo Liu (Chemical Engineering Journal, 2025)

Rice straw–derived biochar-enriched biodegradable mulch film for enhancing soil organic carbon - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Bioresource Technology Reports, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Single-cell transcriptomic analysis reveals immune remodeling in bone marrow during aged sepsis - Yijia Lin; Zhiying Zhou; Mingkun Yang; Yingzheng Weng; Zhouxin Yang; Jing Yan (GeroScience, 2025)

Analysis of cellular and gene therapy product reviews in the United States - Cheng-Fang Weng; Jhe-Yuan Dong; Shiuan-Fei Lin; Ai-Lei Jiang; Yu-Li Cheng; Lin-Chau Chang (Regulatory Toxicology and Pharmacology, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Smoldering heterogeneous oily sludge: Key influencing factors - Yi Lin; Zehua Luo; Fuli Li; Chih-Huang Weng; Yanru Hao; Na Liu; Mei Hong (Journal of Cleaner Production, 2025)

Effect of quinone concentration and pH on the structural and functional properties of bovine serum albumin-chlorogenic acid quinone covalent conjugates - Jinshun Ye; Jinqu Wen; Zhenzhao Weng; Yuting Li; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Jingkun Yan; Lin Li (Food Chemistry, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

Internally coupled concave nanobox@quantum dots nanoassemblies for SERS/fluorescence/colorimetric trimodal detection of prognostic biomarker in acute ischemic stroke - Wei-Bin Wang; Jian-Jun Li; Lin-Lin Fan; Jing-Yuan Wang; Guo-Jun Weng; Jian Zhu; Jun-Wu Zhao (Chemical Engineering Journal, 2025)

Homologous nanocellulose modification: A “like cures like” strategy against coffee-ring and infiltration effects in paper-based colorimetric detection - Linan Sun; Yafei Lou; Siyu Chen; Hongyue Weng; Jiahao Li; Zhihui Lin; Junfei Tian; Rong Cao (Analytica Chimica Acta, 2025)

Bioactive scalarane sesterterpenoids and polybrominated diphenyl ethers from the two sponges Hippospongia sp. and Dysidea sp. - Chen You-Ying; Sung Ping-Jyun; Weng Jing-Ru; Chun-Lin Chen; Su Jui-Hsin (Phytochemistry Letters, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Inhibition of transforming growth factor β signaling by prodigiosin through disruption of receptor recycling and subcellular translocation in epithelial cells - Chun-Lin Chen; Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Photothermal actuator based on Nb4C3Tx@CNF composite for bionic applications and wireless cargo transportation - Sitong Zeng; Zhen Wang; Junjie Lin; Nuozhou Yi; Peidi Zhou; Qiaohang Guo; Mingcen Weng; Kaihuai Yang (Chemical Engineering Journal, 2025)

Synergistic HRP/Biotin encapsulation in DNA nanoflowers via RCA: A path to stabilized, streamlined ELISA platform - Xinglin Wu; Chengqun Chen; Chenchen Lin; Jiabin Wang; Qibiao Weng; Xucong Lin (Analytica Chimica Acta, 2025)

Effect of increased temperature on halocarbon emission and bioelectricity generation by Synechococcus sp. UMACC 371 in a biophotovoltaics device - Jing-Ye Tee; Fiona Seh-Lin Keng; Fong-Lee Ng; Gill Malin; Choon-Weng Lee; Siew-Moi Phang (Algal Research, 2025)

Genomic insights into the phylogeny and evolutionary history of scale insects (Hemiptera: Coccoidea): Resolving family-level relationships - Jun Deng; Xianghao Weng; Wentao Ma; Lin Zhang; Chen Wang; Qingsong Zhou; Jiangtao Zhang; Xubo Wang; Xiaolei Huang (Molecular Phylogenetics and Evolution, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

One-pot synthesis of highly stable CsPbBr₃@C6H7NO3S composite and its application in nitrite fluorescent sensing - Yongzhen Qiu; Yexin Zu; Yating Zhang; Yue Lin; Fang Luo; Zuquan Weng; Cuiying Lin; Jian Wang; Bin Qiu; Zhenyu Lin (Food Chemistry, 2025)

Integration of antibacterial itaconic acid derived carbon dots into asiaticoside hydrogel with antioxidant ability for controllable and effective treating Pseudomonas aeruginosa infected burn wound - Yao Wang; Rongjie Lin; Chengwei Zhang; Shuwei Lin; Kai Peng; Chengjie Lin; Min Chen; Yanjie Zheng; Zongfu Zheng; Shaohuang Weng (Chemical Engineering Journal, 2025)

Advancements in gas-liquid separation based on membrane contactors: Critical factors enhancing separation efficiency - Helin Wang; Tao Zhang; Ruochen An; Lin Sun; Xiaohui Weng; Zhiyong Chang (Process Safety and Environmental Protection, 2025)

Integrating microbial community dynamics and emerging contaminants (ECs) for precisely quantifying the sources in groundwater affected by livestock farming - Kai Liu; Jinrong Qiu; Chih-Huang Weng; Zhongen Tang; Renchuan Fu; Xiaojun Lin; Xiujuan Wang; Na Liu; Jingwen Zeng (Journal of Hazardous Materials, 2025)

Assessment of Bacillus cereus spoilage potential and the antibacterial mechanism of Larimichthys crocea-derived peptide SDH73 against Bacillus cereus - Jing Wu; Guanglei Wei; Ritian Jin; Rong Lin; Wuyin Weng; Duo Liang; Xujian Qiu; Shen Yang (International Journal of Food Microbiology, 2025)

Brain White Matter Changes in Non-demented Individuals with Color Discrimination Deficits and Their Association with Cognitive Impairment: A NODDI Study - Jiejun Zhang; Peilin Huang; Lin Lin; Yingzhe Cheng; Weipin Weng; Jiahao Zheng; Yixin Sun; Shaofan Jiang; Xiaodong Pan (Neuroscience Bulletin, 2025)

Developmental toxicity and environmental risk assessment of chlorothalonil: A comprehensive study using biomphalaria as a model gastropod - Hongyu Li; Ruiqi Weng; Hao Wu; Xianwei Li; Jiyuan Wang; Jialu Xu; Qingzhi Zhao; Yunhuan Zhu; Yuncheng Qian; Yijie Zhang; Xiaofen Zhang; Lijun Lin; et al. (Journal of Hazardous Materials, 2025)

Structural characterization and fermentation of a novel Moringa oleifera leaves polysaccharide with hypoglycemic effects - Yuxi Wen; Yang Zhou; Jiaxiang Xu; Qi Cui; Zebin Weng; Yajuan Lin; Haizhao Song; Ling Xiong; Luanfeng Wang; Chao Zhao; Xinchun Shen; Fang Wang (Food Chemistry, 2025)

Genomic analysis of the novel Stenotrophomonas phage vB_Srh_LBjhp91a, isolated from a Karst cave in China - Lou Ren; Zheng Fang; Shixia Li; Qingshan Wu; Lan Xiang; Chuangen Lin; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2025)

Changes of food-cue processing in major depressive disorder patients with decreased appetite: An event-related potential study - Shanshan Lin; Yiwei Du; Yujie Xia; Cai Nan; Shenhong Weng; Lin Zhou; Ling Xiao; Gaohua Wang (Appetite, 2025)

Significance of temperature and salinity in the dynamics of diatoms and dinoflagellates along the coastal Yellow Sea - Chenshi Weng; Dongsheng Ding; Qian Yang; Lin Zhu; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Progress in Oceanography, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

Protease-hydrolysis-driven approach towards the quantification of cellular mRNA after drug treatment in protein nanopores - Ling Zheng; Jizhen Lin; Wenqiang Tian; Ting Weng; Xu Wang; Lan Sun; Chaker Tlili; Xiaohan Chen; Junzhong Lai; Baoquan Zhao; Deqiang Wang (Analytica Chimica Acta, 2025)

New insights into the effects of PFOS exposure on rat lung development: morphological, functional, and single-cell sequencing analysis - Jiali Mo; Jingye Zuo; Lin Yu; Huishan Zhang; Shuting Weng; Leping Ye (Archives of Toxicology, 2025)

Current research on the regulation of glycolipid metabolism by plant-derived active polysaccharides - Jiaxiang Xu; Zebin Weng; Qi Cui; Wen Yu; Yajuan Lin; Haizhao Song; Ling Xiong; Luanfeng Wang; Xinchun Shen; Fang Wang (Trends in Food Science & Technology, 2025)

Faraday cage-type photocurrent polarity switching photoelectrochemical sensing platform for highly selective and sensitive detection of Vibrio parahaemolyticus - Qingqing Zhang; Tingting Zhai; Yuxin Guo; Yifan Weng; Nan Zhou; Han Lin; Hao Tan; Kangning Lu; Yiyi Zhou (Food Chemistry, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Integrated BIM-IoT platform for carbon emission assessment and tracking in prefabricated building materialization - Xiaojuan Li; Ming Jiang; Chengxin Lin; Rixin Chen; Meng Weng; C.Y. Jim (Resources, Conservation and Recycling, 2025)

Highly sensitive aggregation-induced electrochemiluminescence sensor for cadmium detection in Ganoderma lucidum - Zhi-Hong Xu; Xin Weng; Sha-Sha Wang; Ze-Hao Huang; Wen Xu; Wei Xu; Yu Lin; Hang Gao (Food Chemistry, 2025)

Effect of myosin-kappa carrageenan pickering emulsions on the quality of bighead carp surimi gels - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2025)

Groundwater Level Prediction by Wavelet Deep Learning with Smart Pumping Data - Tsai-Ning Weng; Ray-Shyan Wu; Tzu-Han Weng; Yi-Ho Chen; Tsai-Chun Lai; Jui-Yun Hsieh; Chu-Chun Hsu; Yuan-Chien Lin (Water Resources Management, 2025)

Effect of 4-methylbenzoquinone concentration on its covalent conjugates with β-lactoglobulin: Structural and functional properties - Jinshun Ye; Xiaotong Li; Zhenzhao Weng; Yuting Li; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Jingkun Yan; Lin Li (Food Chemistry, 2025)

Exploring the nuanced correlation between built environment and the integrated travel of dockless bike-sharing and metro at origin-route-destination level - Huapeng Shen; Jiancheng Weng; Pengfei Lin (Sustainable Cities and Society, 2025)

Tunable siloxane-induced amphiphilic interphase for high-performance gel polymer–based sodium metal batteries - Jialin Lin; Weiping Li; Pei Huang; Suting Weng; Tuoya Naren; Chengzuo Gong; Chaoping Liang; Weijie Li; Yuejiao Chen; Libao Chen; Chunxiao Zhang; Xuefeng Wang; et al. (Science Bulletin, 2025)

BCP4: A novel antimicrobial peptide with potent efficacy against Bacillus cereus in rice porridge - Weihong Tao; Wenjie Li; Ritian Jin; Duo Liang; Wuyin Weng; Rong Lin; Shen Yang (International Journal of Food Microbiology, 2025)

In-situ reconstruction of active bismuth for enhanced CO2 electroreduction to formate - Chenchen Weng; Cheng Wang; Yang Song; Yu-Xiao Zhang; Kang Zou; Hongwu Chen; Xue Yang; Wei Lin (Chemical Engineering Journal, 2025)

Optimization by artificial neural network and modeling of ultrasound-assisted flavonoid extraction from Phyllanthus emblica L. based on deep eutectic solvents - Xiaolan Weng; Yuli Luo; Fei Pan; Huixin Pan; Zizhao Lao; Zuoyi Lin; Xiaolin Huang; Jiajun Xu; Xuwei Liu (Food Bioscience, 2025)

Reactive oxygen species-sensitive fenofibrate-loaded dextran nanoparticles in alleviation of osteoarthritis - Weibei Sheng; Shuai Liao; Siyang Cao; Yihao Wei; Jin Zhao; Yaohang Yue; Haotian Qin; Tiantian Qi; Junyu Qian; Jianjing Lin; Jian Weng; Yingqi Chen; et al. (Carbohydrate Polymers, 2025)

Deciphering the key drivers of oxidative potential during ammonium nitrate-mediated aqueous-phase photoreaction of methoxyphenols - Racliffe Weng Seng Lai; Tian Qiu; Xuyang Zhang; Yalin Wang; Tianwei Hao; Xinlei Ge; Lin Du; Mingjin Tang; Ka In Hoi; Kai Meng Mok; Yong Jie Li (Atmospheric Environment, 2025)

GWAS analysis revealed genomic loci and candidate genes associated with the 100-seed weight in high-latitude-adapted soybean germplasm - Javaid Akhter Bhat; Hui Yu; Lin Weng; Yilin Yuan; Peipei Zhang; Jiantian Leng; Jingjing He; Beifang Zhao; Moran Bu; Songquan Wu; Deyue Yu; Xianzhong Feng (Theoretical and Applied Genetics, 2025)

The Jinchang deposit, Ailaoshan Belt: overprint of Miocene orogenic gold mineralization on Triassic hydrothermal nickel sulfide mineralization - Huajian Li; Qingfei Wang; David Groves; Chaoyi Dong; Weijun Weng; Wei Ma; Lin Yang; Ziqing Zhu; Jun Deng (Mineralium Deposita, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Novel Pickering emulsions using polysaccharide-myosin complexes: Effect of polysaccharide types - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

A low-molecular-weight α-glucan from edible fungus Agaricus blazei Murrill activates macrophage TFEB-mediated antibacterial defense to combat implant-associated infection - Qishan Wang; Yuehong Wang; Yihao Liu; Kai Yuan; Yixuan Lin; Xian Qian; Hongyan Pei; Liangliang Weng; Kaijian Fan; Yihe Hu; Yiqi Yang (Carbohydrate Polymers, 2024)

New insight into Clostridium butyricum-ferroferric oxide hybrid system in exogenous carbon dioxide-assisted anaerobic fermentation for acetate and butyrate production - Panyu Li; Zhiwen Lin; Chenyi Li; Qingyi Luo; Sishuo Weng; Yue Zeng; Zhenzhen Lan; Wei Wang; Yongkui Zhang (Bioresource Technology, 2024)

Exploring the link between metformin use and adhesive capsulitis of the shoulder: a retrospective cohort study in Taiwan - Bing-Sian Lin; Wu-Chien Chien; Chieh-Hua Lu; Chi-Hsiang Chung; Chang-Huei Tsao; Tzu-Hsuan Weng; Ching-Yueh Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Pancreatic cancer-derived exosomal miR-510 promotes macrophage M2 polarization and facilitates cancer cell aggressive phenotypes - Tao Wang; Lin Ye; Yingjie Zhou; Xionghan Zhang; Renjian Li; Yi Zhou; Jun Weng; Qingrong Mo; Yaqun Yu (Human Cell, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Control of crustal deformation on orogenic Au mineralization in Himalaya: A case study from Buzhu - Chaoyi Dong; Qingfei Wang; Daniel D. Gregory; Huajian Li; Weijun Weng; Lin Yang; Jun Deng (Journal of Structural Geology, 2024)

Green energy meets urban agriculture: Unveiling the carbon reduction potential of Rooftop Agrivoltaics - Qunyue Liu; Taoyu Chen; Ni Zhang; Zubin Ye; Kunneng Jiang; Zhiqian Lin; Yaling Gao; Yourui Guo; Aifang Weng (Journal of Cleaner Production, 2024)

Low voltage electrostatic field combined with ice-temperature to improve the quality of litchi during storage - Junping Zhou; Jijun Wu; Haoran Liu; Xian Lin; Lina Cheng; Chuyuan Li; Shaoquan Weng; Min Zhao; Yujuan Xu; Jing Wen (Food Research International, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

Robust self-healing ion-conductive interlocking dual-network binder based on gradient dynamic bonding for advanced SiO anodes in Li-Ion batteries - De He Weng; Liu Zhen Wu; Zi Feng He; Dong Yu Zhu; Yuan Li; Bole Ma; Qiyu Liu; Liheng Chen; Zhan Lin; Xueqing Qiu (Chemical Engineering Journal, 2024)

In-situ fabrication of defect rich Cu2+1O on electrodeposited Cu cone arrays for promoting electrocatalytic anode hydrogen production - Yanhong Weng; Huanhua You; Danni Liu; Hao Chen; Hao Lin; Guodong Fu; Fengzhan Si; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Cuproptosis in microsatellite stable colon cancer cells affects the cytotoxicity of CD8+T through the WNT signaling pathway - Jintao Zeng; Hong Chen; Xing Liu; Haoyun Xia; Liqi Chen; Dajia Lin; Naisen Wang; Chong Weng; Guoxian Guan; Yu Zheng (Chemico-Biological Interactions, 2024)

Characteristics and stabilization of Pickering emulsions constructed using myosin from bighead carp (Aristichthys nobilis) - Jiafei Wang; Min Lin; Linfan Shi; Yongqiang Zhao; Shuji Liu; Zhiyu Liu; Rong Lin; Ritian Jin; Wuyin Weng; Zhongyang Ren (Food Chemistry, 2024)

An Anisotropic Thermal–Mechanical Coupling Failure Criterion for Slate - Meng-Chia Weng; Shih-Shiang Lin; Chih-Shan Lee; Wei-Han Wu; Jia Han Li; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2024)
This study investigates the thermal–mechanical behavior of slates in geothermal reservoirs and establishes an anisotropic thermal–mechanical coupling failure criterion. Slate samples obtained from a geothermal site were subjected to a series of direct-shear and triaxial-compression tests at various confining pressures and temperatures. The results showed that the orientation angle within a specific range caused shear sliding failure of the slate, primarily due to foliation strength; beyond this range, intrinsic rock properties led to different failure modes. Elevated temperatures significantly diminished the strength anisotropy of the slate. These findings provided a foundation for the development of an anisotropic thermal–mechanical coupling failure criterion. The validity of the proposed criterion, which incorporates both the orientation angle and thermal degradation effects, was demonstrated through experimental results. A three-dimensional surface diagram was constructed to visualize the relationship between the temperature, orientation angle, and failure principal stress, highlighting the anisotropic thermal-degradation characteristics of the slate under varying confining pressures. This study enhances the understanding of the thermal–mechanical behavior of these materials in geothermal reservoirs.

Altered Cortical Information Interaction During Respiratory Events in Children with Obstructive Sleep Apnea-Hypopnea Syndrome - Jin Chen; Minmin Lin; Naikai Shi; Jingxian Shen; Xuchu Weng; Feng Pang; Jiuxing Liang (Neuroscience Bulletin, 2024)

Association Between the Serum Copper Levels and Environmental Tobacco Exposure on the Risk of Overweight and Obesity in Children: a Study Based on the National Health and Nutrition Examination Survey - Yujun Luo; Linzhu Zhang; Yanting Lu; Xiaohong Lin; Zelin Weng; Youjia Xu (Biological Trace Element Research, 2024)

Greenhouse gas emissions and carbon and water footprints during processing of Lei bamboo shoots - Zixiang Weng; Shuiqin Lu; Xuekun Cheng; Chunyu Pan; Guangyu Wang; Dejin Dong; Zhengcai Li; Ziliang Zhao; Lei Gu; Linghui Dong; Zhengwen Niu; Chong Li; et al. (Journal of Cleaner Production, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Molecular separation-assisted label-free SERS combined with machine learning for nasopharyngeal cancer screening and radiotherapy resistance prediction - Jun Zhang; Youliang Weng; Yi Liu; Nan Wang; Shangyuan Feng; Sufang Qiu; Duo Lin (Journal of Photochemistry and Photobiology B: Biology, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

The role of galectins in the regulation of autophagy and inflammasome in host immunity - Tzu-Han Lo; I-Chun Weng; Hung-Lin Chen; Fu-Tong Liu (Seminars in Immunopathology, 2024)

Stefin B alleviates the gouty arthritis in mice by inducing the M2 polarization of macrophages - Shishui Lin; Xu Hu; Yang Li; Jiyue Huang; Rui Zhang; Xinxin Bai; Shaohuang Weng; Min Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The present study aims to explore the therapeutic effect of Stefin B on gouty arthritis (GA) and the polarization of macrophages in mice. Stefin B-overexpressed or knockdown M0 macrophages were constructed. The GA model was established in mice by injecting 25 mg/mL MSU, followed by a single injecting of Stefin B-overexpressing adenovirus vector (GA model + Stefin B OE) or an empty vector (GA model + Stefin B OE NC). Stefin B was found lowly expressed in M1 macrophages. CD206 was markedly upregulated and IL-10 release was signally increased in Stefin B-overexpressed macrophages. In gouty arthritis mice, marked redness and swelling were observed in the ankle joint. Dramatical infiltration of inflammatory cells was observed in the GA model and GA model + Stefin B OE NC groups, which was suppressed in the Stefin B OE group. Increased proportion of F4/80 + CD86 + cells observed in GA mice was markedly repressed by Stefin B overexpression, accompanied by the declined level of Caspase-1 and IL-17. Collectively, Stefin B alleviated the GA in mice by inducing the M2 polarization of macrophages.

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

Machine learning-enabled high-throughput industry screening of edible oils - Peishan Deng; Xiaomin Lin; Zifan Yu; Yuanding Huang; Shijin Yuan; Xin Jiang; Meng Niu; Weng Kung Peng (Food Chemistry, 2024)

Methane sink of subterranean space in an integrated atmosphere-soil-cave system - Guangneng Zeng; Wangbiao Lu; Yanwei Wang; Haijun Peng; Ping Chen; Xu Weng; Jia Chen; Lin Zhang; Haijun Du; Weijun Luo; Shijie Wang (Environmental Research, 2024)

Evaluating the anisotropic thermal–mechanical coupling strength of slate: A discrete element method approach - Minh-Triet Pham; Meng-Chia Weng; Hoang-Khanh Le; Shih-Shiang Lin; Wei-Han Wu (Computers and Geotechnics, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Ingenious approach for retrieving valuable metals from gypsum via dehydration–rehydration two-step phase transition - Jiayi Zheng; Changzhou Weng; Chen Tian; Wenchao Zhang; Jiemin Qin; Xiaoqin Li; Weizhen Liu; Jing Zhang; Zhang Lin (Chemical Engineering Journal, 2024)

Exploring the evolution of coupled natural-cultural ecosystem services and their geographically scaled driven modeling in a coastal city of Southeast China - Linsheng Wen; Baoyin Li; Yun Peng; Yunrui Zhou; Aifang Weng; Yidong Jin; Guo Cai; Yuying Lin; Baibi Chen (Journal of Environmental Management, 2024)

Identification of antibiotic-resistance markers of Edwardsiella tarda using aptamers - Yunting Fan; Jiang Zheng; Mao Lin; Qibiao Weng; Lixing Huang; Qingpi Yan (Food Bioscience, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Gluing blood into adhesive gel by oppositely charged polysaccharide dry powder inspired by fibrin fibers coagulation mediator - Yan Fang; Yukai Lin; Linyu Wang; Qinhui Chen; Yunxiang Weng; Haiqing Liu (Carbohydrate Polymers, 2024)

The Impact of Offshore Photovoltaic Utilization on Resources and Environment Using Spatial Information Technology - Peng Wang; Jingru Zhou; Xinfei Jin; Jingchao Shi; Ngai Weng Chan; Mou Leong Tan; Xingwen Lin; Xu Ma; Xia Lin; Kaixuan Zheng; Jiexuan Wu; Fei Zhang (Journal of Marine Science and Engineering, 2024)
In recent years, the rapid development of the photovoltaic (PV) industry has resulted in a saturation of research on onshore PV power plant construction. However, current studies on the impact of marine PVs on the marine environment remain limited and scarce. In order to facilitate the implementation of carbon reduction goals and promote the sustainable development of the offshore PV industry, this study analyzes the environmental impact of PV sea-use resources based on spatial information technology in the western part of Gaotang Island. The findings show that the MIKE21FM model provides relatively accurate simulations of tidal flow and tide level in the marine PV area. Flow velocity in the marine PV area exhibits a decreasing trend, with an average decrease ranging from 0.03 to 0.07 m/s. This decrease minimally affects surrounding navigational channels and large-scale flow fields. The resulting siltation is also deemed less significant, with an annual deposition from 0.03 to 0.06 m/a. Moreover, offshore PV construction resulted in a total intertidal biological loss of 123.45 t. The suspension of sediment during cofferdam construction and removal has a potential effect on zooplankton and fishery resources. Overall, it is proposed that careful planning, prudent site selection, and the execution of countermeasures during marine PV construction will combine to minimize the impact on the marine environment.

Performance and mechanistic studies of rapid atenolol degradation through peroxymonosulfate activation by V, Co, and bamboo carbon catalyst - Yihui Hu; Kai Yang; Yule Lin; Xin Weng; Yanting Jiang; Jian Huang; Yuancai Lv; Xiaojuan Li; Yifan Liu; Chunxiang Lin; Minghua Liu (Environmental Science and Pollution Research, 2024)

Insight into the imbalance of forest cover change at county level in mainland China during 2000–2020: From the perspective of subdividing forest cover change into forest gain and loss - Yuying Lin; Xueman Zuo; Aifang Weng; Mir Muhammad Nizamani; Yidong Jin; Linsheng Wen; Qing Zhao; Baoyin Li (Journal of Cleaner Production, 2024)

Anhydride esterification to regulate water migration and reduce ice crystal formation in κ-carrageenan gel during freezing - Xinwei Xu; Feng Jiang; Kuncheng Lin; Jingjing Fang; Fuquan Chen; Yi Ru; Huifen Weng; Qiong Xiao; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Enhanced peroxymonosulfate (PMS) activation process mediated by vanadium modified CoO catalyst for rapid degradation of organic pollutants: Insights into the role of V - Yanting Jiang; Xin Weng; Yihui Hu; Yuancai Lv; Zhendong Yu; Yifan Liu; Xiaojuan Li; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2024)

Punching shear behavior and corrosion resistance of composite slab-column connections reinforced by BFRP and steel rebar - Kai Qian; Yun-Hao Weng; Shi-Lin Liang; Feng Fu (Engineering Structures, 2024)

Transplantation of MiR-28-5p-Modified BMSCs Promotes Functional Recovery After Spinal Cord Injury - Zhen Li; Haitao Su; Guandai Lin; Kai Wang; Yongming Huang; Yaqian Wen; Dan Luo; Yu Hou; Xuewei Cao; Jiaxian Weng; Dingkun Lin; Le Wang; et al. (Molecular Neurobiology, 2024)
Traumatic spinal cord injury (TSCI) is a prevalent central nervous system condition that imposes a significant burden on both families and society, affecting more than 2 million people worldwide. Recently, there has been increasing interest in bone marrow mesenchymal stem cell (BMSC) transplantation as a promising treatment for spinal cord injury (SCI) due to their accessibility and low immunogenicity. However, the mere transplantation of BMSCs has limited capacity to directly participate in the repair of host spinal cord nerve function. MiR-28-5p, identified as a key differentially expressed miRNA in spinal cord ischemia–reperfusion injury, exhibits differential expression and regulation in various neurological diseases. Nevertheless, its involvement in this process and its specific regulatory mechanisms in SCI remain unclear. Therefore, this study aimed to investigate the potential mechanisms through which miR-28-5p promotes the neuronal differentiation of BMSCs both in vivo and in vitro. Our results indicate that miR-28-5p may directly target Notch1, thereby facilitating the neuronal differentiation of BMSCs in vitro . Furthermore, the transplantation of lentivirus-mediated miR-28-5p-overexpressed BMSCs into SCI rats effectively improved footprint tests and Basso, Beattie, and Bresnahan (BBB) scores, ameliorated histological morphology (hematoxylin–eosin [HE] and Nissl staining), promoted axonal regeneration (MAP2 and growth-associated protein 43 [GAP43]), and facilitated axonal remyelination (myelin basic protein [MBP]). These findings may suggest that miR-28-5p-modified BMSCs could serve as a therapeutic target to enhance the behavioral and neurological recovery of SCI rats.

Exploring nanoparticle emissions and size distributions during incense burning and filtration in an indoor space - Hsi-Hsien Yang; Wei-Cheng Weng; Yong-Wen Chen; Xuan-Yi Lin; Ying I. Tsai (Air Quality, Atmosphere & Health, 2024)

Research on anchoring force of the deep-sea stratum drilling robot - Peihao Zhang; Jiawang Chen; Yongqiang Ge; Xingshuang Lin; Xiaoling Le; Zixin Weng; Ziqiang Ren (Marine Georesources & Geotechnology, 2024)

Nonlinear effects of surface soil moisture changes on vegetation greenness over the Tibetan plateau - Wenwen Li; Denghua Yan; Baisha Weng; Yuequn Lai; Lin Zhu; Tianling Qin; Zhaoyu Dong; Wuxia Bi (Remote Sensing of Environment, 2024)

Exploring the spatiotemporal relationships between built environment and the public transport competitiveness: A case study from Beijing - Jiancheng Weng; Huapeng Shen; Pengfei Lin; Yunqi Jing; Huimin Qian (Journal of Cleaner Production, 2024)

LC-MS/MS-assisted label-free SERS blood analysis by self-position plasmonic platform for tumor screening - Min Fan; Kaiming Peng; Youliang Weng; Yuanmei Chen; Qiyi Zhang; Minqi Lin; Duo Lin; Yudong Lu; Shangyuan Feng (Chemical Engineering Journal, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

Metro systems: Construction, operation and impacts - Dong Lin; Zhipeng Zhou; Miaocheng Weng; Wout Broere; Jianqiang Cui (Tunnelling and Underground Space Technology, 2024)

Electric field as extracellular enzyme activator promotes conversion of lignocellulose to humic acid in composting process - Lu Zhang; Xuan Wang; Hongge Wang; Yubo Cao; Liping Weng; Lin Ma (Bioresource Technology, 2024)

Optimizing automated feeder algorithms for feed intake prediction in barramundi (Lates calcarifer) - Richard Le Boucher; Weiqiang Chung; Jessalin Ng Kai Lin; Lydia Shun En Tan; Zhi Weng Josiah Poon; Co Sin Lee (Aquaculture, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Emission of volatile halocarbons from the farming of commercially important tropical seaweeds - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Hui-Yin Yeong; Gill Malin; Emma Leedham Elvidge; William Sturges; Choon-Weng Lee (Journal of Applied Phycology, 2023)

Health and economic benefits of reducing air pollution embodied in GBA's green and low-carbon development - Yang Xie; Xiaorui Liu; Danyang Li; Mengdan Zhao; Zhixiong Weng; Lin Zhang; Meng Xu (Urban Climate, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Influence of sidewall restriction on flame characteristics of double fires in a channel - Shengzhong Zhao; Kai Du; Yongzheng Yao; Fei Wang; Miaocheng Weng; Lin Xu; Wenjun Lei (Tunnelling and Underground Space Technology, 2023)

Adsorption and reduction behavior and mechanism of Au(III) on reductive cellulose-based aerogel - Rengui Weng; Guohong Chen; Yifan Liu; Yuancai Lv; Chunxiang Lin; Xiaoxia Ye; Minghua Liu (Process Safety and Environmental Protection, 2023)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

Chromium removal from chromium gypsum through microwave hydrothermal crystal phase regulation - Chengzhe Liao; Xiaoqin Li; Jun Li; Jiayi Zheng; Changzhou Weng; Weizhen Liu; Zhang Lin (Environmental Science and Pollution Research, 2023)

Properties of Pacific white shrimp (Litopenaeus vannamei) collagen and its degradation by endogenous proteinases during cold storage - Xu-Chen Xiao; Duanquan Lin; Kai-Yuan Cao; Le-Chang Sun; Yu-Lei Chen; Ling Weng; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2023)

Disseminated gold mineralization under varied redox conditions: Constraints from microscopic observation, geochemistry, and thermodynamic modeling on fluid-rock interactions in lamprophyres, Zhenyuan gold deposit - Huajian Li; Qingfei Wang; Lin Yang; Weijun Weng; Jun Deng (Chemical Geology, 2023)

Oxygen-induced dual-signal point-of-care testing aptasensor for aflatoxin B1 detection using platinum nanoparticle catalysis in visual fluorometry and gravimetry - Fang Luo; Linxiu Zhan; Ye Deng; Kun Qiao; Nan Pan; Zuquan Weng; Cuiying Lin; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2023)

A review on processing methods and functions of wheat germ-derived bioactive peptides - Zebin Weng; Yuanrong Chen; Tingting Liang; Yajuan Lin; Hui Cao; Haizhao Song; Ling Xiong; Fang Wang; Xinchun Shen; Jianbo Xiao (Critical Reviews in Food Science and Nutrition, 2023)

Fully bio-based fire-safety composite from cotton/viscose wastes and alginate fiber as furniture materials - Lin Weng; Xiaolin Zhang (Waste Management, 2023)

Potential modulation of Nickel-Cobalt hydroxide nanosheets with conductive Poly(3,4-Ethylenedioxythiophene) skin for aqueous hybrid supercapacitors - Man Wang; Qiang Liu; Juan Yang; Kai Jiang; Siyu Liu; Xiaogang Che; Qingsong Weng; Junxiong Wu; Dongmei Lin; Jieshan Qiu; Guohua Chen (Chemical Engineering Journal, 2023)

Systematic optimization of biochars derived from corn wastes, pineapple leaf, and sugarcane bagasse for Cu(II) adsorption through response surface methodology - Kesinee Iamsaard; Chih-Huang Weng; Jing-Hua Tzeng; Jin Anotai; Astrid R. Jacobson; Yao-Tung Lin (Bioresource Technology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

High-enthalpy biphasic phase change organogels with shape memory function based on hydrophobic association and H-bonding interaction - Chenxiao Yin; Zhi-Xiong Fei; Jingrui Sun; Lin Weng; Xu Wang; Ke-Ke Yang; Ling-Ying Shi (Chemical Engineering Journal, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Investigating the nonlinear and non-stationary relationship between PM2.5 and air pollutants by wavelet signal analysis in central Taiwan - Shan-Non Feng; Yi-Ho Chen; Tzu-Han Weng; Yuan-Chien Lin (Environmental Geochemistry and Health, 2023)

Comparative Life Cycle Assessment (LCA) on battery electric and combustion engine motorcycles in Taiwan - Falk Schneider; Daniel Sebastián Castillo Castro; Kuo-Che Weng; Cheng-Hsiang Shei; Hsin-Tien Lin (Journal of Cleaner Production, 2023)

Three-dimensional porous AuNPs-decorated polyaniline array for ultrasensitive determination of trace Cd(II) and Pb(II) in drinking water - Guodong Zhu; Chengwei Feng; Lin Wang; Chenkai Zhou; Xiaole Weng; Kun Yang (Journal of Environmental Chemical Engineering, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

Fast and visual detection of nucleic acids using a one-step RPA-CRISPR detection (ORCD) system unrestricted by the PAM - Kangfeng Lin; Jianguang Guo; Xiangju Guo; Qinghan Li; Xiao Li; Zhen Sun; Zehang Zhao; Jiao Weng; Jinzhun Wu; Rui Zhang; Boan Li (Analytica Chimica Acta, 2023)

Submarine groundwater discharge in Dongshan Bay, China: A master regulator of nutrients in spring and potential national significance of small bays - Yafei Sun; Guizhi Wang; Yubin Weng; Qing Li; Fei Zhang; Weizhen Jiang; Guiyuan Dai; Wen Lin; Shengyao Sun; Yiyong Jiang; Yuanjing Zhang (Frontiers in Marine Science, 2023)
Despite over 90% of China’s coastal bays have an area less than 500 km 2 , the geochemical effects of SGD on those ecosystems are ambiguous. Based on mapping and time-series observations of Ra isotopes and nutrients, a case study of small bays (<500 km 2 ), we revealed that submarine groundwater discharge (SGD) predominately regulated the distribution of nutrients and fueled algal growth in Dongshan Bay, China. On the bay-wide scale, the SGD rate was estimated to be 0.048 ± 0.022 m day −1 and contributed over 95% of the nutrients. At the time-series site where the bay-wide highest Ra activities in the bottom water marked an SGD hotspot with an average rate an order of magnitude greater, the maximum chlorophyll concentration co-occurred, suggesting that SGD may support the algal bloom. The ever-most significant positive correlations between 228 Ra and nutrients throughout the water column (P< 0.01, R 2 > 0.90 except for soluble reactive phosphorus in the surface) suggested the predominance of SGD in controlling nutrient distribution in the bay. Extrapolated to a national scale, the SGD-carried dissolved inorganic nitrogen flux in small bays was twice as much as those in large bays (>2,000 km 2 ). Thus, the SGD-carried nutrients in small bays merit immediate attention in environmental monitoring and management.

Association between co-exposure of polycyclic aromatic hydrocarbons and chronic obstructive pulmonary disease among the US adults: results from the 2013–2016 National Health and Nutrition Examination Survey - Lin Wen; Xiaosong Ben; Zhiyu Yang; Yingying Wu; Yuxuan Tan; Qian Chen; Huanzhu Liang; Yexin Li; Xiaomei Wu; Shan Liu; Xueqiong Weng; Dan Tian; et al. (Environmental Science and Pollution Research, 2023)

Association between blood metal exposures and hyperuricemia in the U.S. general adult: A subgroup analysis from NHANES - Yuxuan Tan; Yingyin Fu; Feng Huang; Lin Wen; Xueqiong Weng; Huojie Yao; Huanzhu Liang; Mincong Kuang; Chunxia Jing (Chemosphere, 2023)

Low-crystalline Ni(OH)2 ultrathin nanosheets upcycled from solid wastes for efficient photoconversion of low-concentration CO2 - Bin Han; Yuanfang Lin; Yu Luo; Weizhen Liu; Xueming Liu; Zonglin Weng; Xinwen Ou; Zhang Lin (Chemical Engineering Journal, 2023)

Towards effective wildlife protection law for marine species in China: A stakeholders’ perspective - Kit Yue Kwan; Ruifang Chen; Chun-Chieh Wang; Shuhao Lin; Lv Wu; Xiaoyong Xie; Zhaohong Weng; Menghong Hu; Haichao Zhou; Zhou Wu; Yijian Fu; Wenquan Zhen; et al. (Frontiers in Marine Science, 2023)
Introduction As one of the megadiverse countries, the effectiveness of wildlife protection in China is of great significance to global biodiversity conservation. With continued evolution and revisions, China’s Wildlife Protection Law has listed over 140 marine species; however, it is still inclined toward terrestrial animals. Methods To narrow the gap between compliance and enforcement, we collected 1,309 effective responses from various coastal cities of China through an anonymous online questionnaire survey, to investigate their exposure, understanding and attitudes toward Wildlife Protection Law for marine species (mWPL). Results Most respondents demonstrated an overall good understanding about the context, necessity and effectiveness of mWPL. The fisher communities were found to be more aware of the dissemination and implementation of mWPL. However, they understood less of the penal system, and exhibited negative attitudes toward the necessity and punishment of the legislation, probably due to the conflicts between resource utilizations and legislative interventions. The participants also indicated that seahorses, horseshoe crabs and corals were commonly subjected to illegal exploitations. Discussion While most respondents suggested greater fines, tighter laws and better public enforcement, we advocate the exploration of bottom-up options such as community engagement and environmental education to improve compliance and implementation of mWPL for the benefit of marine wildlife conservation in China.

Mining the synergistic effect in hydrothermal co-liquefaction of real feedstocks through machine learning approaches - Jie Yu; Xiaomei Zhong; Zhilin Huang; Xiaoyu Lin; Haiyong Weng; Dapeng Ye; Quan (Sophia) He; Jie Yang (Fuel, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Fixing sulfur dioxide by feeding calcine oxide into the rotary volatilization kiln in zinc smelting plant - Wei Weng; Wenze Zhang; Hongfu Lin; Xiaopeng Chi; Shuiping Zhong (Environmental Science and Pollution Research, 2023)

Online evaluation of catalytic co-pyrolysis of hemicellulose and polypropylene over CaO catalyst - Junjie Weng; Zhanjun Cheng; Yi Zhang; Chao Jiang; Lin Long; Jian Wang; Jianfeng Pan (Fuel, 2023)

Simulation Study on the Sediment Dispersion during Deep-Sea Nodule Harvesting - Yuan Lin; Zixin Weng; Jin Guo; Xingshuang Lin; Nhan Phan-Thien; Jian Zhang (Journal of Marine Science and Engineering, 2022)
During the harvesting of polymetallic nodules on the seabed, the sediment plume due to disturbance on the seabed impacts the benthic ecosystem. A numerical simulation based on the SPH (smooth particle hydrodynamics) method is used to estimate the time and length scale of the plume impact near the seabed during a small-scale harvesting process. The simulation result considerably agrees with the one from the lab-scale water-channel experiment. It is found that, in the sediment plume, the traced sub-plume with iso-surface of lower sediment concentration travels a longer distance, and spends a longer time to achieve the stable state. Moreover, with the increase of the releasing rate of the disturbed sediment, the sub-plume spreads over greater distance, which also needs more time to achieve the stable state.

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

Associations of single and multiple organophosphate pesticide exposure with female infertility in the USA: data from the 2015–2018 National Health and Nutrition Examination Survey - Yingying Wu; Xueqiong Weng; Shan Liu; Yuxuan Tan; Huanzhu Liang; Yexin Li; Lin Wen; Qian Chen; Chunxia Jing (Environmental Science and Pollution Research, 2022)

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Relationship between urinary dichlorophenols and cognitive function among people over 60 years old from NHANES - Xueqiong Weng; Huanzhu Liang; Kun Liu; Jingmin Chen; Qiaoyuan Fei; Shan Liu; Xinrong Guo; Lin Wen; Yingying Wu; Zhiqiang Nie; Chunxia Jing (Environmental Science and Pollution Research, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Towards less invasive molecular diagnostics for endometrial cancer: massively parallel sequencing of endometrial lavage specimens in women attending for an office hysteroscopy - Angel Chao; Kai-Yun Wu; Chiao-Yun Lin; Yun-Shien Lee; Huei-Jean Huang; Yun-Hsin Tang; Cindy Hsuan Weng; An-Shine Chao; Ting-Chang Chang; Chyong-Huey Lai; Ren-Chin Wu (Journal of Molecular Medicine, 2022)

SGBNet: An Ultra Light-weight Network for Real-time Semantic Segmentation of Land Cover - Kai Pang; Liguo Weng; Yonghong Zhang; Jia Liu; Haifeng Lin; Min Xia (International Journal of Remote Sensing, 2022)

Meta-analysis of the associations of IMPDH and UGT1A9 polymorphisms with rejection in kidney transplant recipients taking mycophenolic acid - Lin Cheng; Pu Yao; Bangbi Weng; Ming Yang; Qian Wang (European Journal of Clinical Pharmacology, 2022)

Perfusion Defects and Collateral Flow Patterns in Acute Small Subcortical Infarction: a 4D Dynamic MRI Study - Yen-Chu Huang; Jiann-Der Lee; Yi-Ting Pan; Hsu-Huei Weng; Jen-Tsung Yang; Leng-Chieh Lin; Yuan-Hsiung Tsai (Translational Stroke Research, 2022)
The hemodynamic changes of acute small subcortical infarction (SSI) are not well understood. We evaluate the hemodynamic changes and collaterals in acute SSI using perfusion magnetic resonance imaging (MRI). A total of 103 patients with acute SSI in penetrating artery territories were recruited and underwent MRI within 24 h of stroke onset. Using 4D dynamic perfusion MRI, they were divided into three patterns: 25 (24%) with normal perfusion, 31 (30%) with compensated perfusion, and 47 (46%) with hypoperfusion. The development of anterograde or retrograde collaterals was also evaluated. Patients with hypoperfusion pattern had the highest rate of early neurological deterioration (32%, p = 0.007), the largest initial and final infarction volumes ( p < 0.001 and p = 0.029), the lowest relative cerebral blood flow (0.63, p < 0.001), and the lowest rate of anterograde and retrograde collaterals (19%, p < 0.001; 66%, p = 0.002). The anterograde collaterals were associated with higher relative cerebral blood volume (0.91 vs. 0.77; p = 0.024) and a higher rate of deep cerebral microbleeds (48 vs. 21%; p = 0.028), whereas retrograde collaterals were associated with higher systolic and diastolic blood pressure ( p = 0.031 and 0.020), smaller initial infarction volume (0.81 vs. 1.34 ml, p = 0.031), and a higher rate of lobar cerebral microbleeds (30 vs. 0%; p = 0.013). Both anterograde and retrograde collaterals may play a critical role in maintaining cerebral perfusion and can have an impact on patient clinical outcomes. Further studies are warranted to verify these findings and to investigate effective treatments.

Rainfall Variability Index (RVI) analysis of dry spells in Malaysia - Yuk Feng Huang; Ali Najah Ahmed; Jing Lin Ng; Kok Weng Tan; Pavitra Kumar; Ahmed El-Shafie (Natural Hazards, 2022)

Mixed effects of perfluoroalkyl and polyfluoroalkyl substances exposure on cognitive function among people over 60 years old from NHANES - Xueqiong Weng; Huanzhu Liang; Yuxuan Tan; Jingmin Chen; Qiaoyuan Fei; Shan Liu; Xinrong Guo; Lin Wen; Yingying Wu; Chunxia Jing (Environmental Science and Pollution Research, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Evaluating coupled hydromechanical behavior of anisotropic rock mass using DEM - Wen-Jie Shiu; Meng-Chia Weng; Chia-Chi Chiu; Po-Lin Wu (Bulletin of Engineering Geology and the Environment, 2022)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

LINC00200 contributes to the chemoresistance to oxaliplatin of gastric cancer cells via regulating E2F1/RAD51 axis - Mengxin Lin; Meifang Xu; Zongbin Xu; Zongqi Weng; Bingqiang Lin; Yanqin Lan; Qing Liu; Xiaoyan Lin; Jie Pan (Human Cell, 2021)

In Memory of Leslie G. Ungerleider - Ning Liu; Hui Zhang; Xilin Zhang; Jiongjiong Yang; Xuchu Weng; Lin Chen (Neuroscience Bulletin, 2021)

Evaluating the effect of midpalatal corticotomy-assisted rapid maxillary expansion on the upper airway in young adults using computational fluid dynamics - Juan Li; Lingfang Shi; Xiayao Zhang; Luxi Weng; Hong Chen; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2021)

Facile Microwave-Assisted Synthesis of Functionalized Carbon Nitride Quantum Dots as Fluorescence Probe for Fast and Highly Selective Detection of 2,4,6-Trinitrophenol - Shikong Lu; Meihua Xue; Aojia Tao; Yuhui Weng; Bixia Yao; Wen Weng; Xiuchun Lin (Journal of Fluorescence, 2021)

Doxorubicin metabolism moderately attributes to putative toxicity in prodigiosin/doxorubicin synergism in vitro cells - Shian-Ren Lin; Chun-Shu Lin; Ching-Cheng Chen; Feng-Jen Tseng; Tsung-Jui Wu; Lebin Weng; Ching-Feng Weng (Molecular and Cellular Biochemistry, 2020)
Doxorubicin (Dox) is a widely neoplasm chemotherapeutic drug with high incidences of cardiotoxicity. Prodigiosin (PG), a red bacterial pigment from Serratia marcescens , has been demonstrated to potentiate Dox’s cytotoxicity against oral squamous cell carcinoma cells through elevating Dox influx and identified as a Dox enhancer via PG-induced autophagy; however, toxicity of normal cell remains unclear. This study is conducted to evaluate putative cytotoxicity features of PG/Dox synergism in the liver, kidney, and heart cells and further elucidate whether PG augmented Dox’s effect via modulating Dox metabolism in normal cells. Murine hepatocytes FL83B, cardio-myoblast h9c2, and human kidney epithelial cells HK-2 were sequentially treated with PG and Dox by measuring cell viability, cell death characteristics, oxidative stress, Dox flux, and Dox metabolism. PG could slightly significant increase Dox cytotoxicity in all tested normal cells whose toxic alteration was less than that of oral squamous carcinoma cells. The augmentation of Dox cytotoxicity might be attributed to the increase of Dox-mediated ROS accumulation that might cause slight reduction of Dox influx and reduction of Dox metabolism. It was noteworthy to notice that sustained cytotoxicity appeared in normal cells after PG and Dox were removed. Taken together, moderately metabolic reduction of Dox might be ascribed to the mechanism of increase Dox cytotoxicity in PG-induced normal cells; nevertheless, the determination of PG/Dox dose with sustained cytotoxicity in normal cells needs to be comprehensively considered.

Altered properties of brain white matter structural networks in patients with nasopharyngeal carcinoma after radiotherapy - Qinyuan Chen; Xiaofei Lv; Shufei Zhang; Jiabao Lin; Jie Song; Bolin Cao; Yihe Weng; Li Li; Ruiwang Huang (Brain Imaging and Behavior, 2020)

Correction to: Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2020)
After publication in volume [37], issue [1], page [94–101] the authors decided to opt for Open Choice and to make the article an open access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2018 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Experimental study and engineering application of slurry permeability mechanism of slurry shield in circular-gravel stratum - Dongshuang Liu; Xinrong Liu; Chengqian Lin; Fei Xiong; Yafeng Han; Qingjun Meng; Zuliang Zhong; Qiang Chen; Chengxian Weng (Arabian Journal of Geosciences, 2020)

Macrophage–NLRP3 Inflammasome Activation Exacerbates Cardiac Dysfunction after Ischemic Stroke in a Mouse Model of Diabetes - Hong-Bin Lin; Guan-Shan Wei; Feng-Xian Li; Wen-Jing Guo; Pu Hong; Ya-Qian Weng; Qian-Qian Zhang; Shi-Yuan Xu; Wen-Bin Liang; Zhi-Jian You; Hong-Fei Zhang (Neuroscience Bulletin, 2020)

(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata - I-Ting Weng; Yen-An Lin; Guan-Yu Chen; Hsiu-Mei Chiang; Yi-Jung Liu; Chao-Jung Chen; Yu-Hsuan Lan; Chia-Lin Lee (Natural Product Research, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Identification of Candidate Growth-Related SNPs and Genes Using GWAS in Brown-Marbled Grouper (Epinephelus fuscoguttatus) - Yang Yang; Lina Wu; Xi Wu; Bijun Li; Wenhua Huang; Zhuoying Weng; Zixuan Lin; Leling Song; Yin Guo; Zining Meng; Xiaochun Liu; Junhong Xia (Marine Biotechnology, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Failure mechanism of a mudstone slope embedded with steep anti-dip layered sandstones: case of the 2016 Yanchao catastrophic landslide in Taiwan - Cheng-Han Lin; Ching Hung; Meng-Chia Weng; Ming-Lang Lin; Ryosuke Uzuoka (Landslides, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

A thiopyran derivative with low murine toxicity with therapeutic potential on lung cancer acting through a NF-κB mediated apoptosis-to-pyroptosis switch - Liping Chen; Bixia Weng; Huimin Li; Haonan Wang; Qian Li; Xiaoyan Wei; Hui Deng; Sicen Wang; Chengxi Jiang; Renyu Lin; Jianzhang Wu (Apoptosis, 2019)

Land-use scene classification based on a CNN using a constrained extreme learning machine - Qian Weng; Zhengyuan Mao; Jiawen Lin; Xiangwen Liao (International Journal of Remote Sensing, 2018)

The tomato IQD gene SUN24 regulates seed germination through ABA signaling pathway - Lulu Bi; Lin Weng; Zhuyan Jiang; Han Xiao (Planta, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Assessment of potassium speciation in soil using traditional single leaching and modified sequential extraction processes - Chakkrit Poonpakdee; Jing-Hua Tzeng; Chih-Huang Weng; Yao-Tung Lin (Journal of Soils and Sediments, 2018)

Breeding potential of maize germplasm populations to improve yield and predominant heterotic pattern in Northeast China - Hongjun Yong; Zhenguo Jin; Li Gao; Lin Zhang; Xianjun Liu; Fangjun Zhang; Xiaocong Zhang; Degui Zhang; Mingshun Li; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

GATA4 regulates osteoblastic differentiation and bone remodeling via p38-mediated signaling - Tingting Zhou; Shuyu Guo; Yuxin Zhang; Yajuan Weng; Lin Wang; Junqing Ma (Journal of Molecular Histology, 2017)

Midgut morphological changes and autophagy during metamorphosis in sand flies - Juliana Malta; Matthew Heerman; Ju Lin Weng; Kenner M. Fernandes; Gustavo Ferreira Martins; Marcelo Ramalho-Ortigão (Cell and Tissue Research, 2017)

Development of a novel engineered antibody targeting Neisseria species - Chih-Yueh Liu; Chang-Ching Weng; Chih-Hsiang Lin; Chiou-Ying Yang; Kwok-Kong Tony Mong; Yaw-Kuen Li (Biotechnology Letters, 2017)

Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2017)
Exogenous crosslinking has been shown to have potential for treating disc degeneration and back pain due to its ability to increase the strength and toughness of the annulus fibrosus, increase intervertebral joint stability, decrease intradiscal pressure, and increase fluid flow through the disc. Some results imply that crosslink augmentation may also lead to changes in the compressive load sharing properties of the disc. The objective of the present study was to evaluate directional stress distribution changes of the disc following genipin crosslinking treatment. Bovine lumbar motion segments were randomly divided into control and crosslinked groups. Annular strains were determined from simultaneous deformation measurements at various time points during compressive creep testing. Four stress components of the annulus were then calculated according to the previously measured modulus data. Immediately after the application of a 750-N compressive load, mean axial and radial compressive stresses in the crosslinked group were twofold higher than control means. Conversely, mean lamellae-aligned and circumferential tensile stresses of the crosslinked discs were 8- and threefold lower, respectively, compared to control means. After 1-h creep loading, the two compressive mean stresses in both the control and genipin-crosslinked specimens increased approximately threefold from their initial 750-N-loaded values. The two tensile mean stresses in the crosslinked group remained lower than the respective levels of the control means after creep loading. A greater proportion of annular compressive load support under compressive creep loading, with a commensurate decrease in both tensile stresses and strains, was seen in the discs following exogenous crosslink augmentation.

Heterosis and combining ability of seven maize germplasm populations - Xiaocong Zhang; Hongjun Yong; Zhiqiang Zhou; Chaoshu Zhang; Ming Lu; Qi Sun; Lin Zhang; Mingshun Li; Degui Zhang; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Interleukin-17A Acts to Maintain Neuropathic Pain Through Activation of CaMKII/CREB Signaling in Spinal Neurons - Cheng-ye Yao; Ze-lin Weng; Jian-cheng Zhang; Tao Feng; Yun Lin; Shanglong Yao (Molecular Neurobiology, 2016)

Monsoonal and lunar variability in microzooplankton abundance and community structure in the Terusan mangrove creek (Malaysia) - Yu Lin Yong; Li Lee Chew; Choon Weng Lee; Ving Ching Chong (Marine Biology Research, 2016)

Fine mapping of a dominantly inherited powdery mildew resistance major-effect QTL, Pm1.1, in cucumber identifies a 41.1 kb region containing two tandemly arrayed cysteine-rich receptor-like protein kinase genes - Xuewen Xu; Ting Yu; Ruixue Xu; Yang Shi; Xiaojian Lin; Qiang Xu; Xiaohua Qi; Yiqun Weng; Xuehao Chen (Theoretical and Applied Genetics, 2016)

One-step RT-LAMP analysis for efficient detection of Odontoglossum ringspot virus from Oncidiinae hybrids (Orchidaceae) - Chi-Chu Tsai; Chun-Yen Huang; I-Szu Weng; Wen-Lin Liu; Chang-Hung Chou (Journal of General Plant Pathology, 2016)

Production of 2,3-Butanediol from Sucrose by a Klebsiella Species - Fengxue Xin; Anindya Basu; Michelle Cheung Weng; Kun-Lin Yang; Jianzhong He (BioEnergy Research, 2016)

Calreticulin Regulates VEGF-A in Neuroblastoma Cells - Wen-Chin Weng; Kuan-Hung Lin; Pei-Yi Wu; Yi-Chien Lu; Yi-Cheng Weng; Bo-Jeng Wang; Yung-Feng Liao; Wen-Ming Hsu; Wang-Tso Lee; Hsinyu Lee (Molecular Neurobiology, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Development of SNP-based dCAPS markers linked to major head smut resistance quantitative trait locus qHS2.09 in maize - Hong Di; Xianjun Liu; Qiankun Wang; Jianfeng Weng; Lin Zhang; Xinhai Li; Zhenhua Wang (Euphytica, 2015)

Satellite data assimilation of upper-level sounding channels in HWRF with two different model tops - Xiaolei Zou; Fuzhong Weng; Vijay Tallapragada; Lin Lin; Banglin Zhang; Chenfeng Wu; Zhengkun Qin (Journal of Meteorological Research, 2015)

QTL-seq identifies an early flowering QTL located near Flowering Locus T in cucumber - Hongfeng Lu; Tao Lin; Joël Klein; Shenhao Wang; Jianjian Qi; Qian Zhou; Jinjing Sun; Zhonghua Zhang; Yiqun Weng; Sanwen Huang (Theoretical and Applied Genetics, 2014)

Autolysis of krill protein from North Pacific krill Euphausia pacifica during protein recovery via isoelectric solubilization/precipitation - Le-Chang Sun; Yong-Lin Chen; Chan Zhong; Emiko Okazaki; Min-Jie Cao; Wu Yin Weng; Kazufumi Osako (Fisheries Science, 2014)

Involvement of abscisic acid in regulating antioxidative defense systems and IAA-oxidase activity and improving adventitious rooting in mung bean [Vigna radiata (L.) Wilczek] seedlings under cadmium stress - Shi-Weng Li; Yan Leng; Lin Feng; Xiao-Ying Zeng (Environmental Science and Pollution Research, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

Effects of calcium on the activities of cytosolic antioxidative enzymes and IAA oxidase during in vitro adventitious rooting of mung bean seedlings - Shi-Weng Li; Lin Feng; Xiao-Ying Zeng (In Vitro Cellular & Developmental Biology - Plant, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Efficient multi-site-directed mutagenesis directly from genomic template - Fengtao Luo; Xiaolan Du; Tujun Weng; Xuan Wen; Junlan Huang; Lin Chen (Journal of Biosciences, 2012)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

Influence of gonadotropin-releasing hormone agonist on the effect of chemotherapy upon ovarian cancer and the prevention of chemotherapy-induced ovarian damage: an experimental study with nu/nu athymic mice - Qiong-yan Lin; Yi-feng Wang; Hui-nan Weng; Xiu-jie Sheng; Qing-ping Jiang; Zhi-ying Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Selectivity of N170 in the left hemisphere as an electrophysiological marker for expertise in reading Chinese - Jing Zhao; Su Li; Si-En Lin; Xiao-Hua Cao; Sheng He; Xu-Chu Weng (Neuroscience Bulletin, 2012)

Chronic cigarette smoke exposure enhances brain-derived neurotrophic factor expression in rats with traumatic brain injury - I-Neng Lee; Martin Hsiu-Chu Lin; Chiu-Yen Chung; Ming-Hsueh Lee; Hsu-Huei Weng; Jen-Tsung Yang (Metabolic Brain Disease, 2012)

Relationships between photosystem II efficiency and photochemical reflectance index under different levels of illumination: comparison among species grown at high- and low elevations through different seasons - Jen-Hsien Weng; Shau-Lian Wong; Kuan-Ming Lai; Rong-Jhih Lin (Trees, 2012)

VP15R from infectious spleen and kidney necrosis virus is a non-muscle myosin-II-binding protein - Xiaopeng Xu; Ting Lin; Lichao Huang; Shaoping Weng; Wei Wei; Zhongsheng Li; Ling Lü; Zhijian Huang; Jianguo He (Archives of Virology, 2011)

BNIP3 induces IL6 and calcineurin/NFAT3 hypertrophic-related pathways in H9c2 cardiomyoblast cells - Yi-Jiun Weng; Wei-Wen Kuo; Chia-Hua Kuo; Kwong-Chung Tung; Chang-Hai Tsai; James A. Lin; Fuu-Jen Tsai; Dennis Jine-Yuan Hsieh; Chih-Yang Huang; Jin-Ming Hwang (Molecular and Cellular Biochemistry, 2010)

Functional analysis of Spodoptera litura nucleopolyhedrovirus p49 gene during Autographa californica nucleopolyhedrovirus infection of SpLi-221 cells - Tiehao Lin; Mei Yu; Wenbi Wu; Qian Yu; Qingbei Weng; Kai Yang; Meijin Yuan; Yi Pang (Virus Genes, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

Novel Vitamin and Gold-Loaded Nanofiber Facial Mask for Topical Delivery - Anahita Fathi-Azarbayjani; Lin Qun; Yew Weng Chan; Sui Yung Chan (AAPS PharmSciTech, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Quantitative identification of teratoma tissues formed by human embryonic stem cells with TeratomEye - Steve Kah Weng Oh; Pauline Chua; Koh Lin Foon; Emily Ng; Angela Chin; Andre Boon Hwa Choo; Rajagopalan Srinivasan (Biotechnology Letters, 2009)

Uptake of Different Species of Iodine by Water Spinach and Its Effect to Growth - Huan-Xin Weng; Ai-Lan Yan; Chun-Lai Hong; Lin-Li Xie; Ya-Chao Qin; Charles Q. Cheng (Biological Trace Element Research, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

A mismatch process in brief delayed matching-to-sample task: an fMRI study - Xi Zhang; Lin Ma; Shunwei Li; Yuping Wang; Xuchu Weng; Luning Wang (Experimental Brain Research, 2008)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

High expression of capsid protein of red‐spotted grouper nervous necrosis virus in an avian cell line requires viral RNA2 non‐coding regions - J N Huang; L Lin; S P Weng; J G He (Journal of Fish Diseases, 2007)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)

Tie them up tight: wrapping by Philoponella vicina spiders breaks, compresses and sometimes kills their prey - William G. Eberhard; Gilbert Barrantes; Ju-Lin Weng (The Science of Nature, 2006)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Mining the structural knowledge of high-dimensional medical data using isomap - S. Weng; C. Zhang; Z. Lin; X. Zhang (Medical & Biological Engineering & Computing, 2005)

Construction and characterization of a bacterial artificial chromosome library of marine macroalgaPorphyra yezoensis (Rhodophyta) - Dai Yong Deng; Ge Zhao; Jin Song Xuan; Ji Liang Yang; Lin De Duan; Man Li Weng; Bin Wang (Plant Molecular Biology Reporter, 2004)

Molecular assay of novel pasturage, sugarcane-grass 94-42, using RAPD markers - Chen Liang; Lin Nan; Huang Zhen; Weng Pin; Lu Chuanbei; Shen Mingshan (Genetic Resources and Crop Evolution, 2004)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, , C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)